Infrastructure and Employment Creation in the Middle East and North Africa - Freund, Caroline; Ianchovichina, Elena (World Bank, Washington, DC, 2012)
The report estimates Middle East and North Africa's (MENA's) infrastructure investment and maintenance needs through 2020 at 106 billion dollars per year or 6.9 percent of the annual regional gross domestic product (GDP). Developing oil exporting countries (OEC) will need to commit almost 11 percent of their GDP annually ($48 billion) on improving and maintaining their national infrastructure endowments, while the oil importing countries (OIC) and the Gulf Cooperation Council (GCC) oil exporters need approximately 6 and 5 percent of their GDP, respectively. Infrastructure investment has the potential to create jobs quickly, while providing a foundation for future growth. This is especially important in the oil importing countries, where the infrastructure gap is the greatest and employment needs are growing. However, it is also likely to be most difficult in these countries because of strained finances. Going forward, government decisions on what types of spending to expand and what to contract to achieve balanced budgets will have important implications for jobs. Prudent infrastructure development will be critical for short and long-term growth and job creation.